A redescription of Yoyetta landsboroughi (Distant) and Y. tristrigata (Goding and Froggatt) (Hemiptera: Cicadidae) and description of four new related species - Emery, Nathan J.; Emery, David L.; Popple, Lindsay W. (Zootaxa, 2015)
This study provides redescriptions of two small cicada species, Yoyetta landsboroughi (Distant) and Y. tristrigata (Goding and Froggatt), from eastern Australia, based on a detailed morphological examination of available material. The status of Y. toowoombae (Distant) is re-examined and it is now formally recognised to be a junior synonym of Y. landsboroughi. Four new species of Yoyetta are described, also from eastern Australia. These are: Y. cumberlandi sp. nov., Y. fluviatilis sp. nov., Y. nigrimontana sp. nov., and Y. repetens sp. nov.. Within each species (re)description, sections on distinguishing features, distribution, habitat and behaviour, and calling song structures are described and illustrated where appropriate.